Timing Results of 22 yr for PSR J0922+0638 - Peng Liu; Mingyang Wang; Jianping Yuan; Zhonghao Tu; Ang Li; Xia Zhou; Na Wang (The Astrophysical Journal)
We conducted a timing analysis of PSR J0922+0638 (B0919+06) using data from the Nanshan 26 m radio telescope and the MeerKAT telescope, spanning from 2001 January to 2023 March. During this 22 yr period, we discovered a previously unreported small glitch (glitch 1) before the well-known large glitch (glitch 2), occurring at MJD ∼ 53325(3), with a frequency jump amplitude of Δ ν / ν  ∼ 0.79(6) × 10 ^−9 . We also identified 10 slow glitch events, half of which were newly detected. These slow glitches occurred quasi-periodically, with an average interval of approximately 553(21) days, fractional frequency changes ranging from Δ ν / ν  ∼ 1.13(1) × 10 ^−9 to 4.08(5)×10 ^−9 , and a maximum fractional change in the first derivative of the frequency of ${\rm{\Delta }}\dot{\nu }/\dot{\nu }\sim -4.6\times 1{0}^{-3}$ . Additionally, our timing noise analysis reveals a change in the spectral index for noise power before and after glitch 2, with values of −6.0 and −5.3, respectively, likely due to this large glitch. Throughout the entire observation period, the first derivative of the spin frequency ( $\dot{\nu }$ ) showed a periodic structure. The possible modulation period was estimated to be 537(24) days before the 700 days data gap at MJD 56716 and 600(58) days afterward. We discuss the periodic oscillations in pulsar rotation as a possible manifestation of spin-down noise and quasi-periodic slow glitches.